1998
DOI: 10.1046/j.1365-2168.1998.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine in human breast cancer

Abstract: The concentration of histamine in breast cancer was sufficient to inhibit lymphocyte function and could be locally immunosuppressive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…In accordance with previous reports demonstrating higher HDC activity in breast cancer in comparison to normal tissue, [13][14][15] HDC protein expression was significantly augmented in breast carcinomas. Nevertheless, the increase in histamine content observed in carcinomas was not significant.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In accordance with previous reports demonstrating higher HDC activity in breast cancer in comparison to normal tissue, [13][14][15] HDC protein expression was significantly augmented in breast carcinomas. Nevertheless, the increase in histamine content observed in carcinomas was not significant.…”
Section: Discussionsupporting
confidence: 81%
“…[9][10][11][12] High histamine biosynthesis and content has been reported in different human neoplasias including breast cancer, as well as in experimental tumors induced in rodents. 5,[13][14][15] We have previously reported that H1R and H2R are present in different normal and malignant cell lines and benign lesions and tumors derived from human mammary gland. [16][17][18][19][20] Furthermore, in experimental mammary carcinomas, histamine becomes an autocrine growth factor capable of regulating cell proliferation via H1R and H2R.…”
Section: Introductionmentioning
confidence: 99%
“…15 An immunosuppressive role for mast cells in breast cancer, mediated via histamine, has also been postulated. 16 A negative correlation between the number of mast cells present in regional lymph nodes and the presence of breast cancer metastases has been noted, 17 which further suggests a potential inhibitory role for mast cells on tumor growth. This concept has been supported by recent studies in a rat model of breast carcinoma.…”
Section: Mast Cells In Breast Cancer S Dabiri Et Almentioning
confidence: 99%
“…H igh levels of histamine and histidine decarboxylase have been demonstrated in tumor interstitium (13 -15). In addition, high levels of histamine have also been identi ed in human skin, rectal and breast cancer (16)(17)(18)(19) (18). In a recent study evaluating the concentration of histamine in breast cancer, it was concluded that the Table 2 Signi cant lymphocyte in ltration in the two groups concentration of histamine in breast cancer was suf cient to inhibit the lymphocytic function and could be immunosuppressive locally (16).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study evaluating the concentration of histamine in breast cancer, it was concluded that the Table 2 Signi cant lymphocyte in ltration in the two groups concentration of histamine in breast cancer was suf cient to inhibit the lymphocytic function and could be immunosuppressive locally (16). H istamine induces immunosuppression by inhibiting lymphocyte migration (16,20) and reducing the lytic ability of cytotoxic T lymphocytes (9). H istamine also inhibits the natural killer cell activity (21,22).…”
Section: Discussionmentioning
confidence: 99%